The Scopaeus decipiens species group from the East Palaearctic and the Oriental Regions, with redescription of S. velutinus Motschulsky, 1858 - Frisch, Johannes (Zootaxa, 2025)
The Scopaeus decipiens species group (Coleoptera: Staphylinidae: Paederinae: Lathrobiini) is established as a monophyletic group in the Oriental Zoogeographical Region. It includes the four species S. complex Sharp, 1874 (China, Korea, Japan, Taiwan, Vietnam), S. decipiens Kraatz, 1859 (Sri Lanka), S. kritschi spec. nov. (Cambodia, Laos), and S. saaberae spec. nov. (Indonesia, Malaysia). Scopaeus decipiens is revalidated from synonymy with S. velutinus Motschulsky, 1848, which does not belong to the S. decipiens species group. Scopaeus complex, S. decipiens, and S. velutinus are redescribed, and lectotypes designated for them.